"With a little help from my best friend…" : Exploring the social functioning of students with moderate learning difficulties in inclusive educational settings. (2020) - Avramidis, Elias; Aroni, Katerina
Highlights: Students with MLD experience low peer-acceptance within their class. Students with MLD manage to establish one high quality friendship. Students with MLD hold positive perceptions about their best friendship. Students with MLD perceive their best friend as close and supportive. Students with MLD hold more reserved views about some aspects of their best friendship compared to their TD peers. Abstract: This study explores the perceived impact of a high-quality best friendship on the social functioning of 20 socially neglected students with moderate learning difficulties (MLD) attending regular secondary schools and on 20 of their typically developing (TD) classmates of a similar social status. The analysis of the data from the semi-structured interviews conducted indicates that all participating students had managed to establish one close friendship and held positive perceptions about its quality. However, students with MLD expressed more reserved views about some aspects of their best friendship compared to their TD peers. The paper concludes with highlighting the need for schools to actively support socially neglected students to establish close relations and transcend their marginalization.